2015
DOI: 10.1530/eje-14-0815
|View full text |Cite
|
Sign up to set email alerts
|

Betatrophin levels are increased in women with gestational diabetes mellitus compared to healthy pregnant controls

Abstract: Objective: Betatrophin has recently been introduced as a novel adipokine/hepatokine, which promotes pancreatic b cell proliferation and improves glucose tolerance in several mouse models of insulin resistance. However, regulation of betatrophin in gestational diabetes mellitus (GDM), as well as its association with markers of obesity, such as glucose and lipid metabolism, inflammation, and renal function, have not been elucidated. Design and methods: Circulating betatrophin was quantified in 74 women with GDM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 17 publications
3
54
0
Order By: Relevance
“…Interestingly, even after fully adjusting for cardiovascular risk factors age, gender, waist circumference, total/HDL cholesterol ratio and renal function remain significantly correlated with betatrophin. Similar to the above mentioned results correlations of betatrophin and age can be found in recent clinical studies to be either positive [18, 19] or negative [32]. With respect to sex specific differences betatrophin levels have been described to be significantly higher in males [16] as well as in females [11].…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Interestingly, even after fully adjusting for cardiovascular risk factors age, gender, waist circumference, total/HDL cholesterol ratio and renal function remain significantly correlated with betatrophin. Similar to the above mentioned results correlations of betatrophin and age can be found in recent clinical studies to be either positive [18, 19] or negative [32]. With respect to sex specific differences betatrophin levels have been described to be significantly higher in males [16] as well as in females [11].…”
Section: Resultssupporting
confidence: 78%
“…Notably, data on a possible influence of renal function on circulating betatrophin levels are sparse, taking into consideration that study populations were varying largely by age and are affected by different manifestations of the metabolic syndrome that predispose for an impaired renal function. Some smaller studies identified weak positive correlations with serum creatinine levels not reaching statistical significance [8, 13, 32]. One recent Japanese study in diabetic patients found a significant negative correlation of betatrophin and creatinine clearance as well as eGFR (calculation adjusted for Japanese population) that seemed mainly driven by a common association of the two factors with age [19].…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the studies included in the present meta-analysis were shown in Table 1. Of the 8 included studies, three were carried out in Turkey [13, 17, 20], two in China [18, 19], one in Austria [15], one in Poland [16] and one in German [14]. The sample size of these studies ranged from 21 to 97.…”
Section: Resultsmentioning
confidence: 99%
“…Three of the included studies involved in the GDM women with BMI < 28 kg/m 2 [14,20], and the rest five with BMI ≥ 28 kg/m 2 [13, 15–18]. Blood samples for betatrophin measurement were collected in the second [13, 17, 19, 20] or third [1416, 18] trimester of gestation. Except for the study conducted in German that used the American Diabetes Association criteria to carry out GDM diagnosis, all studies used the criteria suggested by International Association for Diabetes in Pregnancy Study Group to diagnose GDM.…”
Section: Resultsmentioning
confidence: 99%
“…22,23 However, it was later shown that betatrophin levels had non-significant positive relation with HOMA-β in control healthy or NDM which is not the case in the current study. 24 The paradoxical results may be related to the following observations; first, duration of T2DM where investigators reported that people with longer duration of diabetes had greater betatrophin levels. 25 Second, half subjects with T2DM receiving medication.…”
mentioning
confidence: 99%